The effects of genre on the lexical richness of argumentative and expository writing by Chinese EFL learners - Heng, Renquan; Pu, Liping; Liu, Xing (Frontiers in Psychology, 2023)
Lexical richness, a crucial aspect in L2 (second language) writing research, has been shown to make a difference to L2 writing performance. Nonetheless, the majority of empirical studies have focused either on one single text type or on the comparison between narrative and non-narrative writing (mostly argumentative writing) in academic contexts, whereas there has been a dearth of research regarding the lexical features pertaining to varied non-narrative writing genres. Considering the cognitive demands intrinsic in different writing task types, this study examined the development of lexical richness, which includes lexical density, lexical variation, and lexical sophistication, in Chinese EFL students’ argumentative and expository compositions over the course of one academic year. Fifty-four participants were asked to write eight compositions (with two genres alternated), four argumentative and four expository, which were parsed via the Syntactic Complexity Analyzer. The results indicated a significant increase in all the three sub-constructs of lexical richness in argumentative compositions over the year, while in expository writings, only lexical density and lexical sophistication demonstrated an increasing trend. And as time went on, the participants in both genres tended to use more frequent words with more senses, more academic words, more bigrams that are more frequently used, and more words that are less familiar and less meaningful. Moreover, the argumentative compositions displayed a higher lexical density than the expository ones while the expository compositions manifested greater lexical variation and lexical sophistication than the argumentative ones. The findings of the study suggest implications for L2 writing teaching and research.